PERAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING ATAS PENGARUH DISIPLIN DAN LINGKUNGAN KERJA TERHADAP PRESTASI KERJA - Ruslan Kaswari (Fakultas Ekonomi Universitas Islam 45, 2021)
This study aims to see the role of job satisfaction on discipline and work environment on work performance. In this study, the population and sample were employees and lecturers of Amik Sigma Palembang, amounting to 11 employees and 24 lecturers, so a total of 35 people. The analysis technique in this study used the Sobel Test. The results showed that the job satisfaction variable could not mediate the influence of work discipline and work environment variables on work performance.